Integrated Marketing Communications as a Media to Increase Interest in Choosing a Private School - Reno Moeliasari Widyaningrum; Retno Tanding Suryandari (Yayasan Riset dan Pengembangan Intelektual, 2023)
This research aims to analyze the influence of integrated marketing communications (website, social media, advertising, public relations and direct marketing) on ??school image. As well as analyzing the influence of school image on interest in choosing a private school. The sample in this study was the parents of 320 students. The data analysis method used is PLS-SEM. This research found that the school website did not have a significant effect on the school's image. Meanwhile, the variables of social media, advertising, public relations and direct selling have a positive and significant effect on the school's image. Then the School Image has a positive and significant effect on interest in choosing a school. The results of the mediation analysis show that school image influences the relationship between IMC elements, namely social media, advertising, public relations and direct marketing, and interest in choosing a school. This research has limitations, namely that this study is limited in scope which has an impact on the generalization of the model in condition. Therefore, care is needed to pay attention to the profile of the background variables behind the test in order to avoid problems with the test results which result in errors in formulating the recommended management policies.